Numerical study of hydrodynamic molecular nanoliquid flow with heat and mass transmission between two spinning parallel plates. (30th November 2020) - Shuaib, Muhammad; Bilal, Muhammad; Qaisar, Salman
Abstract: The current article illustrates a three dimensional hydrodynamics nanoliquid flow between two parallel rotating plates. The ambition of the study is to inquire the combined effects of electric and magnetic field on nanoliquid flow with mass and heat transfer characteristics. The base fluid of water is synthesized with copper oxide CuO nanoparticles. The subsequent arrangement of flow model is reduced to a dimensionless set of equations through similarity approach. For the numerical solution, the transformed equations are further tackled with the MATLAB package boundary value solver (bvp4c). To ensure the accuracy, the outcomes are also simulated by Runge Kutta fourth order method. The nature of velocity, heat, and mass transfer rate versus Reynolds number, electrical parameter, molecular diffusion, magnetic parameter and rotation parameter are sketched and discussed. The growing credit of Dufour and Soret number effectively enhances the mass transfer rate, because due to molecular diffusion, the net flux of molecules from a region of higher concentration to lower concentration increases, as a result mass transfer ratio enhances. It has been concluded that CuO nanoparticles positively effects the molecular energy transmission and can be used for cooling purposes.